Inside Cover: Structured Illumination Microscopy for Superresolution (ChemPhysChem 4/2014). Issue 4 (17th March 2014) - Allen, John R.; Ross, Stephen T.; Davidson, Michael W.
<x xml:space="preserve">Abstract</x> Image of a single section from a 3D multicolor superresolution structured illumination (SR‐SIM) reconstruction of a PtK2 cell (SR‐SIM is reviewed by M. W. Davidson et al. on p. 566). DNA is labeled with DAPI (blue), Vimentin with Alexa Fluor 488 (green), and F‐Actin with Phalloidin conjugated to Alexa Fluor 568 (red).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>